Antiphospholipid Syndrome-Related Pulmonary Embolism: Clinical Characteristics and Early Recognition - Shi, Maojing; Gao, Weibo; Jin, Yuebo; Zhu, Jihong; Liu, Yuansheng; Wang, Tianbing; Li, Chun (Frontiers in Cardiovascular Medicine, 2022)
Background: Pulmonary thromboembolism is a common disease frequently encountered in the emergency room and has a high mortality rate. Antiphospholipid syndrome (APS) is a high-risk factor for recurrent pulmonary embolism (PE). It is critical to effectively apply anticoagulants to avoid the recurrence of thrombotic events. This study aims to identify the clinical characteristics of APS patients with PE (APS-PE) and to develop a risk score for APS in PE patients in the emergency situations. Methods: We retrospectively enrolled 76 PE patients in this study, with 46 patients in the APS-PE group and 30 patients in the non-APS-PE group. We compared differences in demographics, laboratory parameters, and early mortality risk between the two groups. Risk factors for APS-PE were screened using logistic regression analysis. We also developed an early risk score using multivariate analysis weighted points proportional to the β regression coefficient values and calculated its sensitivity and specificity for APS in PE. Results: In the APS-PE group, we observed a higher proportion of males (43.6% vs. 20%), a higher proportion of low-risk patients (58.7% vs. 10%), lower levels of white blood cells and platelets (PLT), longer activated partial thromboplastin time (APTT), and a slight increase in D-dimer levels. Patients who were triple positive for antiphospholipid antibodies (aPLs) were younger. The APTT gradually increased as the number of positive aPLs increased. The risk factors for APS included male (OR=5.565, 95% CI 1.176-26.341), decreased PLT (OR=0.029, 95% CI 0.003-0.330), slightly increased D-dimer (OR=0.089, 95% CI 0.019-0.426), and prolonged APTT (OR=4.870, 95% CI 1.189-19.951). The risk score was named MPDA and included male, PLT, D-dimer and APTT, which can predict APS in PE patients with the AUC at 0.888 (95% CI 0.811-0.965). Conclusion: The risk factors for APS in PE patients are male, low PLT, prolonged APTT and slightly prolonged D-dimer. MPDA is a quantitative scoring system which is highly suggestive of APS in PE patients.